2021
DOI: 10.1590/1516-731320210017
|View full text |Cite
|
Sign up to set email alerts
|

Mapas Conceituais e a Elaboração de Conhecimento Científico na História da Ciência: algumas aproximações teóricas

Abstract: Resumo Este artigo tem por objetivo apresentar aproximações teóricas entre características da técnica de mapeamento conceitual e aspectos da elaboração de conhecimento científico na História da Ciência. Tais aproximações foram exemplificadas por intermédio da construção e análise de um mapa conceitual sobre como, historicamente, o conhecimento foi desenvolvido de forma a resultar na Lei da Inércia. Como conclusão, aspectos estruturais dos mapas conceituais (proposições, estrutura bidimensional, ligações cruzad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…This way, it is an element of CM that allows us to present hierarchically how more general knowledge elaborated by science is specified from agreements or disagreements between different comprehensions developed by humankind along HS (Maximo-Pereira et al, 2021). This understanding of the role of hierarchical organization in a CM on HS is compatible with a view of science as a human construction, in permanent change, being developed based on consensus and dissent within the scientific community.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…This way, it is an element of CM that allows us to present hierarchically how more general knowledge elaborated by science is specified from agreements or disagreements between different comprehensions developed by humankind along HS (Maximo-Pereira et al, 2021). This understanding of the role of hierarchical organization in a CM on HS is compatible with a view of science as a human construction, in permanent change, being developed based on consensus and dissent within the scientific community.…”
mentioning
confidence: 83%
“…The authors aforementioned used CM to illustrate the process of concept change in scientific revolutions. More recently, Maximo-Pereira et al (2021) identified the proximity between the concept mapping technique and the elaboration of science knowledge in HS, pointing out that the CM may be used to represent the historical elaboration dynamic of concepts, laws, and science principles.…”
mentioning
confidence: 99%
“…Subsequently, a conceptual map of the knowledge on the subject was created, which was used as a methodological tool and didactic strategy to problematise and synthesise epistemological and scientific thoughts. 13 The second meeting also had exclusively 13 participants, and involved the following activities: 3) associations around the propositional focal question; 4) discussion of concepts and propositions; The third meeting was for 5) synthesis and validation of ideas for cognitive and collective conceptualisation. For the synthesis, the participants were invited to provide statements that they considered adequate and meaningful to the concept of rehabilitation.…”
Section: Data Collectionmentioning
confidence: 99%
“…The results, with this structure, emphasized the students' sensory memory and exposed new evaluative alternatives in school contexts, such as true or false or multiple-choice tests, game of the seven errors, subjective questions, etc. Regarding data collection, Maximo-Pereira, Souza and Lourenço (2021) gathered their results by means of a summary table, emphasizing the objective of the work, to weave the technical characteristics of concept mapping with concepts from the History of Science, and showing that this didactic resource is a useful tool for educational actions that use concept maps in the area of science teaching.…”
Section: Theoretical Backgroundmentioning
confidence: 99%